O corpo na iconografia cristã : o retábulo de São Vicente de Sarriá (1455-1460) - Silva, Michele Cordeiro da (2017)
Human forms have always been a source of fascination. They appear as the driving force of numerous discussions for the human sciences and also for the visual arts. Throughout history, societies have customarily produced images of the body. These express a